Designing a Digital Business Model for Private Tutoring in Bandung Using Business Model and Value Proposition Canvases - Mochamad Yoga Adijaya; Irfan Dwiguna Sumitra; Khurvalieva Tarmiza Latipovna (Universitas Komputer Indonesia, 2026)
Nowadays, Educational Technology (EdTech) is becoming increasingly more significant for the process of modern instruction, assisting students and parents in many processes. However, local private tutoring providers across Bandung face commercial pressures from expanding national EdTech firms. Because small tutoring micro-enterprises rely on manual administrative workflows and rigid face-to-face instruction, it creates the issue where they struggle to keep pace with changing parent and student preferences. This study examines the baseline (As-Is) operations connected to a local private tutoring enterprise, Les Ngaji Bandung. This is done for the purpose of identifying operational bottlenecks and constructing a scalable digital business model (To-Be). For this purpose, a qualitative case study was applied. This was carried out by means of data collection including semi-structured interviews across internal and external stakeholders, field observations, as well as internal record audits. Empirical validity was cross-checked through source triangulation. In this study, the Business Model Canvas (BMC) and Value Proposition Canvas (VPC) served as analytical tools to enable classification of operational failures. These failures are paper-based administration, hyper-localized customer recruitment, rigid session scheduling, and absent student progress tracking. Based on these findings, a lightweight hybrid digital business model is proposed. This model incorporates WhatsApp Business API, QRIS payment settlement, hyper-local SEO, and a streamlined Learning Management System (LMS). As results, this paper presents an empirical conceptual blueprint. In turn, this gives practical insights for educational micro-enterprises to improve operational efficiency and market relevance.